A Chinese version of the Patient Perceptions of Patient‐Empowering Nurse Behaviours Scale: Reliability and validity assessment in chronically ill patients. Issue 3 (6th August 2018) - Zhou, Chun‐Lan; Wang, Si‐Qi; Wang, Yan‐Fang; Ou, Jie‐Xia; Wu, Yan‐Ni
Abstract: Aims and objectives: To translate the Patient Perceptions of Patient‐Empowering Nurse Behaviours Scale (PPPNBS) into Chinese and to psychometrically test the Chinese version of PPPNBS (PPPNBS‐C) in chronically ill patients. Background: The growing prevalence and burden of chronic illnesses became the driving force for the need of empowerment as an approach to engage patients in self‐management. The PPPNBS was developed to assess patient perceptions of the process of empowerment during hospitalisation. Extending its application to different clinical context and ethnicities is worth pursuing. Design: A cross‐sectional survey. Methods: The PPPNBS was translated according to Brislin's translation guidelines and was culturally adapted. A questionnaire survey was carried out to determine the reliability and validity of the PPPNBS‐C among a total of 517 hospitalised patients with chronic illnesses. Results: The content validity was found to be good with a content validity index of 0.94. Exploratory factor analysis identified six factors explaining 68.56% of the total variance and confirmatory factor analysis confirmed this six‐factor structure. The hypothesised differences were demonstrated through contrasted group comparisons by time since diagnosis and length of hospital stay. The score of the PPPNBS‐C was significantly and positively associated with that of the Client Satisfaction Questionnaire, as was the Self‐Efficacy for Managing Chronic Disease 6‐Item Scale score, providing evidence of convergent validity. The Cronbach's alpha coefficient was 0.960 and the intraclass correlation coefficient was 0.86 for the total scale, explaining good internal consistency and time stability. Conclusions: The PPPNBS‐C has preliminary verification of the validity and reliability and could be useful in measuring patient perceptions of patient‐empowering nurse behaviours. Relevance to clinical practice: The PPPNBS‐C can be applied to chronically ill patients as a metric of the implementation status of patient‐empowering nurse behaviours and can be used as a guide to encourage nurse's intentional utilisation of empowering behaviours.